2016
DOI: 10.2166/washdev.2016.021
|View full text |Cite
|
Sign up to set email alerts
|

Three-phase approach to improve deep groundwater supply availability in the Elidar district of Afar region of Ethiopia

Abstract: This study provides new evidence on the effectiveness of a combined remote sensing and hydrogeological investigation method for deep groundwater development in complex geologic and geomorphologic situations in Ethiopia. The study was undertaken in the Elidar district of the Afar region of Northern Ethiopia. Due to the water availability and vegetation in this district, the majority of the population (total population of 79,000 people and 647,000 head of cattle) are dependent on pastoralist livelihoods. The cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The most appropriate technical intervention in a given area is determined by hydrological, hydrogeological and demographic constraints. For example in some areas of the Kolla groundwater levels can be up to 250 m deep [36][37][38] , well beyond the maximum capacity of a hand-pump (typically 45 m). In these areas motorised boreholes are the only appropriate technological solution.…”
Section: Discussionmentioning
confidence: 99%
“…The most appropriate technical intervention in a given area is determined by hydrological, hydrogeological and demographic constraints. For example in some areas of the Kolla groundwater levels can be up to 250 m deep [36][37][38] , well beyond the maximum capacity of a hand-pump (typically 45 m). In these areas motorised boreholes are the only appropriate technological solution.…”
Section: Discussionmentioning
confidence: 99%
“…In East and Southern Africa, the primary form of extraction of groundwater is through boreholes fitted with handpumps. Recent reviews of the level of functionality of handpumps indicate an increase in non-functionality of the technology due to, in part, the lowering groundwater levels which are occurring because of reduced precipitation and groundwater recharge [8]. According to the IPCC WGII-AR5, "Climate change will amplify existing stress on water availability in Africa."…”
Section: Introductionmentioning
confidence: 99%
“…The methodology uses a combination of remote sensing data combined with ground truthing and appropriate deep groundwater drilling methods. This paper builds on an earlier [8] publication and provides a detailed case study of a deep well identified and drilled within the Jesoma sandstone formation of the Somali region in Ethiopia. This paper argues that development of deeper aquifers that are interconnected with surface and groundwater recharge zones is an effective solution in areas of Ethiopia affected by drought.…”
Section: Introductionmentioning
confidence: 99%
“…UNICEF implemented a 3-phase approach to locating and providing groundwater, as detailed in the paper by Godfrey and Hailemichael (2016). Phase 1 of the approach generated remote-sensing data which was combined in Phase 2 with ground measurements of key hydrogeological parameters to produce the UNICEF model.…”
Section: Introductionmentioning
confidence: 99%
“…The model is a weighted linear combination of hydrogeological parameters including permeability, slope, recharge, and lineament density, which has been calibrated using the expert judgements of local hydrogeologists. Phase 3 comprised the validation of the model through the drilling of production boreholes in sites identified by the UNICEF model (Godfrey and Hailemichael, 2016). The 3-phase approach was developed and implemented in 2015 and 2016 in 12 districts of Ethiopia and resulted in the drilling of 13 productive boreholes .…”
Section: Introductionmentioning
confidence: 99%